4-Octyl Itaconate ameliorates diesel exhaust particle-induced oxidative stress in nasal epithelial cells - Steppuhn, Hanna; Hohenberger, Katja; Mittler, Susanne; Trump, Sonja; Carvalho, Christine; Rauh, Manfred; Wild, Andreas B.; Papadopoulos, Nikolaos G.; Finotto, Susetta (Frontiers in Immunology, 2025)
Background and objectiveParticulate matters such as diesel exhaust particles induce oxidative stress in cells and thereby have a negative impact on health. The aim of this study was to test whether the membrane-permeable, anti-inflammatory metabolite 4-Octyl Itaconate can counteract the oxidative stress induced by diesel exhaust particles and to analyze the downstream-regulated pathways both in human nasal epithelial cells and PBMCs.MethodsHuman nasal epithelial cells were cultured from nasal swabs, and the response of the cells to diesel exhaust particles either alone or in combination with 4-Octyl Itaconatee was investigated using RNA sequencing, qPCR, and cytokine measurement. The presence of reactive oxygen species in the cells was analyzed using CellROX staining and flow cytometric DCFDA assay.ResultsDiesel exhaust particles caused an upregulation of CYP1A1 in nasal epithelial cells. The administration of 4-Octyl Itaconate reduced the reactive oxygen species and increased the expression of antioxidant genes regulated by the transcription factor NRF2, which was also confirmed in PBMCs. IL-6 secretion from NEC was elevated by diesel exhaust particles and reduced when 4-Octyl Itaconate was administered.Conclusion4-Octyl Itaconate can reduce the diesel-exhaust-particle-induced oxidative damage by the activation of NRF2-regulated antioxidative pathways.